1999
DOI: 10.2134/jeq1999.00472425002800040023x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Surface Runoff Losses of Nutrients and Metals from Soils Fertilized with Broiler Litter and Commercial Fertilizer

Abstract: While elevated concentrations of N and P have been observed in surface runoff from broiler litter‐amended fields, impacts of other nutrients in broiler litter such as Ca, K, Mg, Mn, Cu, and Zn have not been identified. A study was conducted on a 4% slope during 1991 to 1993 at Belle Mina, AL, on a Decatur silty clay (clayey, kaolinitic, thermic Rhodic Paleudult) to determine effects of broiler litter (BL) on seasonal transport losses of nutrients and heavy metals in surface water. A corn (Zea mays L.)‐winter r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 0 publications
3
50
0
Order By: Relevance
“…Several studies have investigated the relationship between manure application and P concentrations in surface runoff Shreve et al, 1995;Sauer et al, 2000;Wood et al, 1999).…”
Section: Effects Of Poultry Manure Treatments On Po4-p Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the relationship between manure application and P concentrations in surface runoff Shreve et al, 1995;Sauer et al, 2000;Wood et al, 1999).…”
Section: Effects Of Poultry Manure Treatments On Po4-p Concentrationsmentioning
confidence: 99%
“…The average annual PO4-P concentrations in tile drainage water ranged from 0.009 to 0.038 ppm for PM2 treatment. The highest PO4-P concentrations (two samples of 0.127 ppm and one sample of 0.173) were measured from a total of three samples collected from the PM2 drainage plots within two weeks of the crops being planted in early to late May in 1998 and1999. This highest value measured coincides with an exceptionally high PM2 application rate and manure PO4-P content in 1999 (Table 3), and the second highest annual rainfall amounts recorded during the study period (data not shown).This combination of increased PO4-P applications from poultry manure, increased rainfall amounts, and stage of crop growth likely had a strong impact PO4-P transport to subsurface drainage water.…”
Section: Effects Of Poultry Manure Treatments On Po4-p Concentrationsmentioning
confidence: 99%
“…A substantial number of studies have been conducted to determine the eff ects of N-based broiler litter on corn (Zea mays L.) (Brown et al, 1994;Wood et al, 1999) and cotton growth and yield (Mitchell and Tu, 2005;Sistani et al, 2004;Tewolde et al, 2005Tewolde et al, , 2007. However, accurately determining the availability of broiler litter N to crops is a diffi cult task and infl uenced by many factors, including litter N composition, timing, and soil type (Sharpley et al, 1998).…”
mentioning
confidence: 99%
“…The risk associated with the accumulation of trace metals in soils due to the use of organic wastes includes phytotoxicity and the increased entry of toxic metals into the food chain (Heckman et. 1987) as well as in the deterioration of surface water and groundwater quality (Wood et al 1999). However, the above risks are difficult to assess directly through determining the total contents of metals in the organic wastes because the physico-chemical forms of the metal in the manure strongly affect their mobility, reactivity and availability to plants.…”
mentioning
confidence: 99%